Primary myelofibrosis L. - L. M. Meshcheryakova; O. V. Porotkova; L. G. Kovaleva; L. Yu. Kolosova; S. N. Bychkova (Онкогематология)
Literature data of idiopathic myelofibrosis are presented: classification, diagnostic criteria, morphological and molecular features. Particular attention is given to therapy of various clinical forms of primary myelofibrosis.